Ответы и объяснения

2013-12-17T16:37:52+00:00
1(х+2)(х+3)=x^2+5x+6                                                                                                      (x^2+5x+6)(x+8)=x^3+13x^2+46x+48                                                                              (x^3+13x^2+46x+48)(x+12)x^4+25x^3+202x^2+600x+576                                                202x^2-4x^2=198x^2                                                                                                               202x^2-4x^2=198x^2                                                                             198x^2-198x^2=0
это все хорошо, но ответа у тебя нет.
2013-12-17T18:19:58+00:00